Cone geometry optimization and thermal behavior for lithium-ion battery separators - Miranda, D. (2020)
A 3D cone separator geometry for lithium-ion batteries has been optimized taking into account the increase of radius size of one side. Theoretical simulations have been carried out for evaluating the influence of radius size in the cone structure at different discharge rates (1 C and 60 C) in which it was also determined the produced ohmic heat. The value of the discharge capacity in the cone structure depends on the increases of the radius, which is correlated with the electrolyte volume and interface between free electrolyte/cathode. The optimum balance of these parameters is essential for obtaining higher battery performance through this geometry that can be used in the next generation of lithium-ion batteries